The Internalization of Anti-Corruption Values as Hidden Curriculum in Gontor Educational System - Ahmad Muqorobin; Usamah Abdurrahman (Nadwa: Jurnal Pendidikan Islam, 2021)
Corruption is admitted by several scholars as a main factor causing the decline of nations and, in the huger scale, civilizations. It is reasonable that this extraordinary crime disrupts the society in all aspects ranging from political to social. Therefore, nowadays, all entities struggle to identify the more effective methods lead to corruption eradication. In this regard, the education of anti-corruption values, then, is recognized as an appropriate way to preventing individuals from corruptive acts based on his own consciousness. This paper tries to examine the methods of Darussalam Gontor Islamic Institution in educating students, as agent of change, the values of anti-corruption by day-to-day activities both inside and outside classroom through hidden curriculum scheme. The data was compiled by interview, observation, and documentation. Using the descriptive-analysis method, it can be concluded that there are various instruments available in Gontor for the internalization of anti-corruption values such as tiered exemplary systems, assignments to manage transparent and accountable santri organizations, strict law enforcement against dishonesty, provision of preventive disciplinary rules, habituation to standing in queues, and environmental conditioning which is full of anti-corruption messages. In addition, materials containing integrity messages is also taught implicitly in various learning materials in the classroom. Such as Al-Mahfudzat, Al-Muthalaah, and Al-Hadith.